2009
DOI: 10.1037/a0015850
|View full text |Cite
|
Sign up to set email alerts
|

Connecting and separating mind-sets: Culture as situated cognition.

Abstract: 5 Hong Kong Chinese; STUDY 6: Americans; STUDY 7: Norwegians; STUDY 8: African-, European-, and Asian-heritage Americans). Meta-analyses (d = .34) demonstrated homogeneous effects across geographic place (East-West), racial-ethnic group, task, and sensory mode-differences are cued in the moment. Contrast and separation are salient individual mind-set procedures, resulting in focus on a single target or main point. Assimilation and connection are salient collective mind-set procedures, resulting in focus on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
211
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 241 publications
(223 citation statements)
references
References 74 publications
8
211
2
2
Order By: Relevance
“…Research on the culture-as-situated-cognition model (Oyserman, Sorensen, Reber, & Chen, 2009) has shown that monocultural Americans are also subject to cultural priming effects and exhibit cognitive responses congruent with the primed individualistic or collectivistic cultural mindsets. In this case, what cultural primes activate is cognitive processes (contrast and separation vs. assimilation and connection), or what has been termed as the individualistic and collectivistic cultural syndromes available in any individual (Kashima, 2009;.…”
Section: Multicultural Acquisitionmentioning
confidence: 99%
“…Research on the culture-as-situated-cognition model (Oyserman, Sorensen, Reber, & Chen, 2009) has shown that monocultural Americans are also subject to cultural priming effects and exhibit cognitive responses congruent with the primed individualistic or collectivistic cultural mindsets. In this case, what cultural primes activate is cognitive processes (contrast and separation vs. assimilation and connection), or what has been termed as the individualistic and collectivistic cultural syndromes available in any individual (Kashima, 2009;.…”
Section: Multicultural Acquisitionmentioning
confidence: 99%
“…Specifically, the research asks whether the language in which a general self-efficacy scale is presented (e.g., Arabic versus English) can activate a distinctive mind-set, and thus shape participants' responses accordingly. Consider, for instance, the NGSE scale (Chen, et al, 2001), which measures one's belief in a general sense of mastery that is not intended to reflect any particular skill, behavior or situation. This instrument includes eight statements, each one containing the pronoun "I", to which a person has to respond by indicating his/her agreement on a 5-point Likert scale from "strongly disagree" to "strongly agree".…”
Section: The Present Studymentioning
confidence: 99%
“…There are general scales that measure an individual's overall sense of personal mastery, task-specific scales that measure competencies related to particular tasks, and domain-specific scales that assess competencies within a designed domain of knowledge and practice. For instance, the New General Self-Efficacy, NGSE, scale (Chen, Gully, & Eden, 2001) is intended to measure a general sense of mastery that is not tied to a particular situation or behavior. General self-efficacy is considered a motivational trait that emerges over a person's lifetime as an aggregate of the successes and failures experienced across domains, tasks, and situations (Bandura, 1997b;Eden, 1988).…”
Section: Page15mentioning
confidence: 99%
See 2 more Smart Citations